Deteksi Dini Serangan Jantung Saat Aktivitas Olahraga - Solehudin Solehudin; Saiful Gunardi (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Background. Heart attacks are difficult to detect early because the symptoms can vary and are not always specific. Not everyone experiences the same symptoms, and often a heart attack can occur without any obvious symptoms. Heart attack is a serious condition and can threaten a person's life. Sports activity, although it has many health benefits, can also increase the risk of heart attack, especially in people who have certain risk factors. The purpose of community service is to carry out counseling activities for early detection of heart attacks during badminton sports.Method. The activities carried out included checking blood pressure and health counseling to members of the badminton sports community Results. Community service activities will be held on August 12, 2023 in the Badminton community at 19.30 - 20.30 WIB. The number of members participating in counseling was 50 people.Conclusion. The knowledge of members of the Badminton community about early detection of heart attacks during exercise has increased after being given counseling.